Scarcity Message Effects on Consumption Behavior: Limited Edition Product Considerations. Issue 10 (October 2015) - Jang, Wonseok Eric; Ko, Yong Jae; Morris, Jon D.; Chang, Yonghwan
ABSTRACT Recently, many luxury brands have begun to launch limited edition (LE) products. When this happens, advertisers implement two typical types of scarcity messages for LE products: limited‐time scarcity (LTS) versus limited‐quantity scarcity (LQS) messages (Cialdini, 2008). Prior research offered empirical evidence that these scarcity messages make consumers feel that LE products are more special, unique, and valuable, and thus, positively influence their evaluation of the product (Aggarwal, Jun, & Huh, 2011). The current study examined the differential effects of LTS and LQS messages on different types of LE products by focusing on consumers' need for uniqueness.